(Online) public denunciation, public incivilities and offence. (November 2022) - Haugh, Michael
Abstract: Public shaming of private figures in everyday settings is amplified through posting denunciations on social media platforms. The aim of this paper is to understand how the conduct of individuals targeted for online public shaming is not only construed as transgressive, but as warranting public denunciation in the first place through posting denunciations of their conduct on social media platforms. Public incivilities in encounters between strangers in public settings are discursively positioned as denounceable through framing that conduct as morally transgressive, which thereby legitimises public denunciation. However, because framing public conduct as transgressive necessarily involves selecting elements from a particular scene for public inspection and evaluation, public denunciations of public incivilities are always open to contestation. Highlights: Public incivilities occur in encounters between strangers in public settings. Public denunciation of public incivilities can occur in situ or online. Conduct is framed as morally transgressive through online public denunciations. Online public denunciations of public incivilities are always open to contestation.